Entrepreneurship Assistance of Citizens with Special Needs Based-Family and Community - Suharsiwi, Suharsiwi; Choirin, Muhammad (CV. BImbingan Belajar Assyfa, 2023)
The problem of the independence of children with special needs when entering adulthood becomes a separate thought for parents. However, problems related to job opportunities are a problem for all graduates, both senior high and tertiary institutions. Job opportunities are limited, while the current government is still busy with unemployment and human resource development issues. Assistance to them is essential, considering that children with special needs are unique. They require a long period to interact with the environment, and sometimes, they struggle to participate fully and effectively like other citizens. The obstacles they face can be heavy, moderate, and light, depending on the characteristics or types of barriers of each individual with special needs. Even though the conditions they experience are mild and they already have several work skills, they often get social rejection in the world of work, or in some cases, these individuals with special needs have difficulty adapting, so they need assistance. This community service program is expected to help find solutions through activities that involve parents. These universities handle citizens with special needs, local governments, and people who care about children with special needs. Parental involvement and support in this program are very much needed, and the Forum Group Discussion (FGD) is the right tool to analyze their needs and get to know their potential in the future.